Research Progress in Biological Characteristics of Fructilactobacillus sanfranciscensis and Its Influence on Fermented Pasta - Guohua ZHANG; Xiaxia HE; Ting LU; Tian SUN; Canlan WANG; Shiwei ZHOU (Shipin gongye ke-ji)
Fructilactobacillus sanfranciscensis, a common used strain in sourdough, is considered as one of the most valuable lactic acid bacteria (LAB) in the sourdough. F. sanfranciscensis has an important impact on the flavor, nutrition, and texture of fermented pasta through its own growth and metabolism as well as its interactions with yeasts in sourdough. Since this strain was isolated in 1971, its taxonomic status has undergone several changes, with the nomenclature changing from Lactobacillus sanfrancisco to Lactobacillus sanfranciscensis, and in 2020 it was identified as Fructilactobacillus sanfranciscensis, and to date, more than 500 research papers related to this strain have been published. Currently, this strain is included in the list of food cultures of the European Food Safety Authority (EFSA) and the list of microbial strains for restricted use in Korea, but it is not yet in the list of microorganisms used in food in China. This paper provides a systematical overview of the current taxonomic status of F. sanfranciscensis as well as its prevalence in sourdough production. Currently, it explores the biochemical and genetic characteristics of this species and their effects on fermented pasta. This review aims to explore the potential of the application of F. sanfranciscensis in sourdoughs for developing standardized sourdough fermentation agents and providing a theoretical basis for the industrialization of traditional fermented pasta.